Ethanol mediated enhancement in bacterial transformation - Sharma, Arun Dev; Singh, Jaspreet; Gill, Prabhjot Kaur (Electronic Journal of Biotechnology, 2007)
In molecular biology, transformation using E. coli as a host plays a key role in synthesizing gene libraries. The present study demonstrated a new ethanol-based method for transformation of plasmid DNA to E. coli. Ethanol at 10% concentration (v/v) showed best results. Further, as compared with traditional CaCl2 method, the transformation rate, using protocol outlined in this study, was very high, suggesting amenable for further applications.